Modul Keanekaragaman Hayati dengan Pendekatan Kearifan Lokal dan Budaya di Kabupaten Purworejo - Fajar Adinugraha; Adisti Ratnapuri (Universitas Indraprasta PGRI Jakarta, 2020)
This article is purposed to describe local and cultural wisdom approaches on biodiversity topics. Furthermore, this article describes the contents and characteristics of the Biodiversity module (handbook) with a local and cultural wisdom approach. The research method is Research and Development (R&D) conducted in 2020. Biodiversity module with local wisdom and culture approach has 15 characteristics, namely containing elements: cover design reflects topics, communicative language, scientific learning, the meaningful learning, critical thinking, innovative, basic literacy especially digital literacy, character education, ethnobiological studies, ethnopedagogy study, 21st century skills, joyful learning through creativity, student centered learning, illustrations/pictures/media that explain the topic, originality of content and presentation, and prioritizes tolerance and not discriminatory. This module is expected to be a media alternative to biological learning by respecting the local wisdom and culture of the nation in order not to fade.